Energy efficient scheduling in data centers - Paul, Debdeep (2016)
The explosive growth of the Internet has resulted in tremendous growth of the data centers which primarily serve as the cloud computing backbones. We consider the practical architecture of a real data center where different types of services are implemented in different tiers. We use Model Predictive Control (MPC) based energy aware scheduling algorithms to address the resource allocation problem for deferrable jobs in such a tiered architecture, where the switching cost is accounted for in two different ways. We compare the performance of these two algorithms with respect to the important performance parameters of cumulative electricity cost, cumulative renewable usage and cumulative number of switchings. We discuss the results to provide some insightful understanding on these issues.